The association between problematic internet use and social anxiety within adolescents and young adults: a systematic review and meta-analysis - Ding, Haiyang; Cao, Bing; Sun, Qixuan (Frontiers in Public Health, 2023)
Objective: Although numerous studies have investigated the association between Problematic Internet Use (PIU) and social anxiety, the findings have no yet reached consistent. The present meta-analysis aims to examine the association between PIU and social anxiety within adolescents and young adults (age range: 14-24 years old).The meta-analysis systematically retrieved the studies prior to September 7, 2023 from Web of Science, PubMed, PsycINFO, Scopus, CNKI, and CQVIP. The meta-analysis based on randomeffects model to conduct the research. Stata Version 17.0 and JASP 16.3.0 was used to analysis.The meta-analysis ultimately included 37 studies (37 effect sizes in total), involving a total of 36013 subjects. Our findings indicated that the overall correlation between PIU and social anxiety was significant positive (r=0.333, 95%CI [0.292, 0.373], p<0.001). Their association was significantly moderated by publication year, measurement tools for PIU and social anxiety but not significantly by culture context, developmental level and gender.This meta-analysis suggests that social anxiety is a predictor of the development of PIU in adolescents and young adults. Furthermore, the study also finds the possibility that contemporary adolescents and youth may exhibit a more "global" behavior pattern, potentially emphasizing fewer differences between cultures, generations and genders.